Expert Assessment of Android based E-Handout on Animal Tissues Structure and Function Materials - Rani Angraini; Rina Widiana; Liza Yulia Sari (Journal Of Biology Education Research (JBER), 2022)
One of the materials that is difficult for students to understand is the material on the structure and function of animal tissues. The learning resources used by the teacher are in the form of student books and LKPD which are designed by themselves. The number of student books provided by the school is still lacking and limited, the limited number of student books is not sufficient for the number of students. So that not all students get textbooks. The purpose of this study is to produce a valid e-handout. This development research uses the Four D model. This research was carried out until the development stage, namely the validity test. The validity test was assessed by a validator consisting of three lecturers and one teacher. The validity test conducted by the material validator, media validator and learning strategy validator on the e-handout developed was very valid (97.3%). From the results of the validity test, it was concluded that the android-based e-handout on the structure and function of animal tissue for class XI SMA students is very valid so that the e-handout can already be used in learning. Research advice, this research is only up to the stage of develop (development). Therefore, it is recommended for further researchers to proceed to the effectiveness stage to test the effectiveness of this Android-based e-handout in the learning process. And then proceed to the dissemination stage (dissiminate). Therefore, it is recommended for further researchers to proceed to the effectiveness stage to test the effectiveness of this Android-based e-handout in the learning process. And then proceed to the dissemination stage (dissiminate). Therefore, it is recommended for further researchers to proceed to the effectiveness stage to test the effectiveness of this Android-based e-handout in the learning process. And then proceed to the dissemination stage (dissiminate).